Annual report 2017: CGIAR Research Program on Water, Land and Ecosystems - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2018)
WLE responds to the growing challenge of natural resource scarcity and degradation of ecosystem services, and is linked to several SDG 2030 targets. In response to these ‘intractable challenges', WLE works to identify more sustainable and equitable agricultural and natural resource management solutions. This is an ambitious and wide-ranging agenda, but a vital one: scarcity and degradation undermine agricultural productivity as well as resilience, with the most negative impacts on the poorest and most vulnerable smallholder farmers, who are often women. This 2017 report demonstrates the multi-dimensional nature of WLE’s work, including WLE’s efforts to work on some of the more demanding, and more recently emergent areas, of cross-sectoral and cross-scale risk, such as how tackling water scarcity requires not only field level interventions, but also effective management of watersheds, how urbanization threatens food production in peri- urban areas, or how agricultural technology is not responding effectively to the feminization of agriculture. WLE has investigated (See: public Annual Report, 2017) how these risks can be turned around to find new and alternative ways of managing natural resources, whether this is through circular economy or nexus solutions or how effective solutions can be brought to scale through a more conducive and equitable enabling environment.